PELATIHAN PEMANFAATAN TEKNOLOGI INFORMASI BERBASIS APLIKASI GOOGLE BAGI PERANGKAT DESA DI KANTOR DESA NGALE KECAMATAN PILANGKENCENG - Setyansah, Reza Kusuma; Murtafiah, Wasilatul; Suprapto, Edy; Apriandi, Davi; Krisdiana, Ika; Lusiana, Restu; Styorini, Meganis; Sekarsari, Kurnia (UNIVERSITAS PGRI MADIUN, 2023)
Abstract. Improving HR skills in the digitalization era has become a basic need in line with the changing paradigm of the COVID-19 pandemic. The other side that can be seen from the implementation of training in the use of information technology that needs to be carried out is the factor of age diversity, and varied educational background levels so it is hoped that with the digitalization training the village administration system can maximize services to the community. In this service, it is addressed to the Gale Village apparatus, Pilangkenceng District, Madiun Regency. The implementation of this training is in order to make Ngale Village provide superior services in the field of information systems. The training activities include an introduction to google drive, google forms, google documents, and spreadsheets. The application of knowledge about Google in administration can also be practiced in making correspondence, financial reports, and digital presentation programs. In this training, there was also an introduction to google sites (simple village websites) which included the practice of opening websites, browsing the internet, and creating village profile content. After the training is complete, the next step will be to provide assistance to village officials in implementing the knowledge that has been obtained during the training. In this community service activity, 13 village officials participated. In the training, he conveyed the relevance of using google drive storage files, compiling google forms, making google meet, google documents, and google spreadsheets. This form of training is designed for beginners and is expected to be an improvement in service to the community. Abstrak. Peningkatan keterampilan SDM pada era digitalisasi telah menjadi kebutuhan yang mendasar seiring perubahan paradigma pandemi covid-19. Sisi lain yang dapat dilihat dari penyelenggaraan pelatihan pemanfaatan teknologi informasi perlu dilaksanakan adalah faktor keberagaman usia, latar belakang tingkat pendidikan yang bervariatif sehingga diharapkan dengan adanya pelatihan digitalisasi sistem administrasi desa dapat memaksimalkan layanan kepada masyarakat. Dalam pengabdian ini ditujukan kepada perangkat desa gale kecamatan pilangkenceng kabupaten madiun. Pelaksanaan pelatihann ini dalam rangka menjadikan desa ngale memberikan pelayanan yang unggul di bidang sistem informasi. Adapun kegiatan pelatihan meliputi pengenalan google drive, google form, google document dan spreadsheet. Penerapan pengetahuan mengenai google dalam administrasi dapat serta dipraktekkan pembuatan surat menyurat, laporan keuangan, dan program presentasi secara digital. Dalam pelatihan ini juga dilakukan pengenalan google sites (website desa sederhana) yang didalamnya terdapat praktek membuka website, browsing di internet, serta pembuatan konten profil desa. Setelah pelatihan selesai, langkah selanjutnya akan diberikan pendampingan kepada perangkat desa dalam pengimplementasian ilmu yang sudah diperoleh selama pelatihan. Dalam kegiatan pengabdian kepada masyarakat ini diikuti oleh 13 orang perangkat desa. Dalam pelatihan menyampaikan keterkaitan penggunaan file penyimpanan google drive, penyusunan google form, membuatan google meet, google dokumen dan google spreadsheet. Bentuk pelatihan ini didesain untuk pemula dan diharapkan kedepannya menjadi peningkatan dalam pelayanan kepada masyarakat.